Mocking and Making: Subjugation and Suppression of Marginalized and the Politics of Identity - Alam, Sohaib; Khalid, Sadaf; Ahmad, Farhan; Keezhatta, Muhammed Salim (Journal of Education Culture and Society, 2021)
Aim. The present study aims at foregrounding the importance of language and discourses advanced to suppress the voices of dissent and minorities. The subtle art of stimulating a psychologically suppressed identity or subjective violence is either through making or mocking historical facts, cultures, and human activities manifesting the concept of authoritarian democracy. Further, the aim of the study is to grasp the sense of constraints between universality and particularity that denounces the ‘reassertion of identity,’ among Indian Muslims. Moreover, the study judiciously examines disguised ‘mechanisms’ employed under authoritarian politics, tech-populism and journalism intending to promote businesses, dissemination of misinformation and contributes to creating an apocryphal human history, social alienation, and to discrediting an individual’s spontaneity. Concept. The innate unity in a democratic society can be actualised either by envisaging or by translating the texts, thoughts, language and actions, which are altogether conceiving distinctive meanings to morality, ethnicity and culture having its relevance in the contemporary context. The paper features multiple trends/cases of how a single-party monologue has weakened pluralism along with the domination of othering the ‘Others’ under racial, cultural, and national particularism. The paper qualitatively investigates different incidents of transcreation of discourse in establishing or reclaiming the identity contextualised in Frantz Fanon’s declaration of ‘reclaiming the past.’ Results and conclusion. An ingenious discussion on dynamic languages, cultures and action enriches with time and individual incidents are discussed in the study. It re-evaluates the significance of revisiting the history to reclaim, reform, and reconstruct malleable identity and ideologies that take years to build, improvise and restore diversity above majoritarian dogmatism in India. Originality. An inquiry into how thoughts, languages, and human action intertwined are to build a complaisant or contemptuous human identity is the idea behind the article. Indeed, the study’s originality depends on sorting and revisiting numerous dimensions of translation and transcreation of languages, linguistic structure, ideology, and political intent in recent times, either subjugating or falsifying facts against the marginalized in India. The attempt is based on analyzing how the shift in knowledge, culture and social identity construction supersede the less powerful. It is practiced through utilizing tech support, popular mass culture and evolves a discourse to manipulate and mobilize human consciousness for commercial and political gains.